Reduction of contact sensitivity reactions to oxazolone in mite-infested mice. - Laltoo, H (1979)
Oxazolone-sensitized mite-infested (SWR-M) and mite-free (SWR-J) mice were challenged with oxazolone on the skin of the neck and shoulder. The migration of radioactively labeled cells to the site of contact sensitivity reaction to oxazolone was significantly less in SWR-M than in SWR-J mice. Serum obtained from SWR-M mice suppressed the extravasation of cells into the skin site of SWR-J mice challenged with oxazolone. The decrease in cellular influx in SWR-M mice occurred in areas of mite infestation (skin of neck and shoulder) as well as in areas not infested with mites (the ears). SWR-M mice also gave evidence of enhanced vascular permeability. A possible role for histamine in the inhibition of contact sensitivity in mite-infested mice is discussed.